2021
DOI: 10.3390/land10060601
|View full text |Cite
|
Sign up to set email alerts
|

Exploring on the Eco-Climatic Effects of Land Use Changes in the Influence Area of the Yellow River Basin from 2000 to 2015

Abstract: The Yellow River is the second largest river in China, and the provinces and cities affected by the Yellow River are called the Yellow River Basin influence area. The relationship between land use and surface thermal effects in the influence area of the Yellow River Basin from 2000 to 2015 was analyzed using MODIS remote sensing data and an energy balance algorithm. The results showed that: (1) net radiation and latent heat flux both increased, and the high value areas were located in the urban expansion areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The YRB spans the three geographical steps of China, with high and low terrain in the west and east, respectively. It is an important ecological corridor connecting the Qinghai-Tibet Plateau, Loess Plateau, and Yellow-Huai-Hai Plain [48]. It is an important ecological region in China [49].…”
Section: Study Areamentioning
confidence: 99%
“…The YRB spans the three geographical steps of China, with high and low terrain in the west and east, respectively. It is an important ecological corridor connecting the Qinghai-Tibet Plateau, Loess Plateau, and Yellow-Huai-Hai Plain [48]. It is an important ecological region in China [49].…”
Section: Study Areamentioning
confidence: 99%
“…Thus, when less energy is used to heat the atmosphere and surface temperature, it corresponds to a cooling feedback or a weak warming feedback. Conversely, lower values of LE − R net equate to a stronger warming feedback [1,7]. The basic research framework is shown in Figure 4.…”
Section: Datasetmentioning
confidence: 99%
“…The process of surface energy exchange is closely related to solar radiation, ecological change and human activities. The influence of these natural and man-made factors on climate change is mainly realized by the change of surface radiation and energy balance [1]. As a major human activity, land use and land cover change (LUCC) can influence ecological climate through biogeochemical processes [2,3], which is one of the driving forces of regional and global climate change [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated urbanization and rapid population growth have exacerbated regional land use changes, which have a key role to play in the problems of climate change and landscape fragmentation [5][6][7]. Land use is considered to be one of Land 2024, 13, 278 2 of 18 the activities by which humans exert the greatest influence on the Earth's land surface, with significant impacts on landscape ecosystems [8,9]. Types of land use form the basic structural units of landscape ecosystems, and the structural stability and functionality of landscapes are considered fundamental to maintaining the continued survival and development of human society [10].…”
Section: Introductionmentioning
confidence: 99%